2017
DOI: 10.1039/c7nr03246c
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and efficient activation of channelrhodopsins expressed in living cells via specifically-bound upconversion nanoparticles

Abstract: Optogenetics is an innovative technology now widely adopted by researchers in different fields of biological sciences. However, most light-sensitive proteins adopted in optogenetics are excited by ultraviolet or visible light which has a weak tissue penetration capability. Upconversion nanoparticles (UCNPs), which absorb near-infrared (NIR) light to emit shorter wavelength light, can help address this issue. In this report, we demonstrated the target selectivity by specifically conjugating the UCNPs with chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…In this experiment, we used surface modication to modify hydrophobic UCNPs into hydrophilic UCNPs. 54,55 The mesoporous silica shell structure obtained by the sol-gel two-phase transfer strategy via surfactant modication can be obviously seen in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, we used surface modication to modify hydrophobic UCNPs into hydrophilic UCNPs. 54,55 The mesoporous silica shell structure obtained by the sol-gel two-phase transfer strategy via surfactant modication can be obviously seen in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Here we show that these materials can also be co-loaded with a photoswitchable drug into living neurons via a patch pipette, and used to control ion channel conductivity. This approach is complementary to those proposed in other studies, with some encasing UCNPs in polymer films placed adjacent to opsin-transfected neurons [22][23][24] , linking UCNPs intimately to ion channels 25,26 , or simply injecting UCNPs into the extracellular space of living mice 27,29 . Our study relies on the physical confinement provided by the intracellular environment to bring the UCNPs into intimate proximity with an azobenzene (AB) photoswitch called AAQ 8 in CA1 neurons in living brain slices.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, both spiropyran 19 and AB 20 photoswitches have been indirectly controlled using UCNP 21 . In parallel to these studies, biological photoswitches (light-gated ion channels [22][23][24][25][26][27][28][29] , and LOV domains 30 ) have been stimulated by the luminescence from UCNPs. Here we show that blue luminescence generated by 975 nm excitation of a NaYF 4 :TmYb nanoparticle can be used to stimulate cis to trans isomerization of the mono quaternary ammonium photoprobe AAQ.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the improvements of UNCP‐based photon‐transducers, localized stimulations could be additional approaches that contribute to more efficient and remote optogenetic manipulations. Recent study from Chen and co‐workers demonstrated that reducing the distance between UCNPs and light‐sensitive ion channel proteins (ChRs) to the molecular level could minimize the NIR energy and achieve highly specific optogenetic stimulation (Figure c) . The demonstrated study provides a generic approach on the basis of specific binding between NAv‐UCNPs and V5‐ChR2m on the cell membrane, which can be further duplicated for various optogenetic systems.…”
Section: Strategies To Improve Upconversion Optogeneticsmentioning
confidence: 91%
“…c) Targeted and efficient activation of ChRs expressed in living cells via specifically bound UCNPs. Reproduced with permission . Copyright 2017, Royal Society of Chemistry.…”
Section: Strategies To Improve Upconversion Optogeneticsmentioning
confidence: 99%